The Analysis Study of Diagnostic Performance and Accuracy of Mammography as Screening and Diagnostic of Breast Cancer: A Comprehensive Systematic Review - Lisa Haerunisa; Doni Noviartha (The International Journal of Medical Science and Health Research, 2025)
Background: Breast cancer is the most commonly diagnosed cancer in women, excluding skin cancer, and the second leading cause of cancer death after lung cancer. Screening mammography, introduced in the mid-1970s, aimed to diagnose breast cancer at earlier stages and reduce disease-specific mortality. This systematic review aims to evaluate the diagnostic performance and accuracy of mammography as screening and diagnostic of breast cancer by analyzing available studies on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Mammography remains a cornerstone in breast cancer screening due to its high specificity and moderate sensitivity. However, the combination of mammography with other modalities such as MRI and ultrasound can enhance diagnostic performance.